The Evolution and Significance of Baanis in Bharatanatyam - Senaviratne, S.; Abeynayake, P. (University of Jaffna, 2024)
This study explores the evolution and significance of Baanis in Bharatanatyam, a classical dance form from India. Baanis, or stylistic schools, play a pivotal role in shaping Bharatanatyam's repertoire, techniques, and aesthetics, each reflecting distinct regional diversity, historical influences, and creative innovations. The research problem centers on understanding how these stylistic variations have developed and their impact on the continuity and transformation of art forms. This study uses a historical and analytical research design to examine key Baanis such as the Tanjavur Quartet's structured compositions and Vazhuvur's narrative richness. Through a review of historical documents, dance literature, and interviews with practitioners, the study analyzes the factors contributing to the evolution of Baanis, including migration, patronage, and social change. The findings reveal that each Baani offers a unique artistic perspective, serving as an instructional framework and source of individual expression for dancers. The study underscores the role of Baanis as custodians of classical heritage while highlighting their adaptability to contemporary context, thus bridging tradition and innovation. Reflecting broader social and national needs, the research emphasizes the importance of preserving these stylistic schools to maintain cultural diversity and promote artistic creativity. By documenting and analyzing the evolution of Baanis, this study provides valuable insights for dancers, educators, and cultural historians, fostering a deeper understanding of Bharatanatyam’s rich heritage and its dynamic evolution in response to the changing socio-cultural landscape.
Keywords: Artistic Evolution; Bharathanatyam; Baanis; Cultural Heritage; Stylistic School